The Value of Restorative Justice in Balinese Customary Criminal Law in Cases of Sexual Violence - Putri, I Gusti Ayu Kabhita Julia; Gorda, A A A Ngurah Tini Rusmini (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines sexual violence as a serious human rights violation that affects victims physically, psychologically, and socially, including within indigenous communities in Bali. The handling of sexual violence cases therefore requires a legal approach that goes beyond punishment and emphasizes victim recovery while maintaining social harmony. In this context, Balinese customary criminal law, which is rooted in local wisdom, offers restorative justice values that merit critical examination within the national legal framework. Purposes of the Research: The purpose of this study is to analyze the values of restorative justice embedded in Balinese customary criminal law in addressing cases of sexual violence and to assess their relevance and compatibility with Indonesia’s national legal system, particularly in relation to victim protection and human rights standards. Methods of the Research: This research employs normative juridical legal research using a literature study approach. The study analyzes primary legal materials, including statutory regulations, and secondary legal materials such as books, academic journals, and official reports to examine restorative justice principles in Balinese customary criminal law. Results of the Research: The findings show that restorative justice values have long existed in Balinese customary criminal law through mechanisms emphasizing harmony and social balance. However, their application in sexual violence cases reveals normative tensions, as customary settlements may marginalize victims’ rights. This study contributes original insight by critically positioning Balinese customary law as a complementary, not substitutive, mechanism to national criminal law in ensuring victim-centered justice.